A gene mapping bottleneck in the translational route from zebrafish to human - Klein, Niek de; Ibberson, Mark; Crespo, Isaac; Rodius, Sophie; Azuaje, Francisco (Frontiers in Genetics, 2015)
Among a diversity of animal models of disease, the zebrafish is a promising model organism for enabling novel translational biomedical research. To fully achieve the latter, a key requirement is to match molecular readouts measured in zebrafish with information relevant to health and disease in humans. A fundamental step in this direction is to accurately map gene sequences from zebrafish to humans. Despite significant progress in genome annotation, this remains an intricate and time-consuming challenge. Here we discuss major obstacles that we had to overcome to systematically map genes from zebrafish to human. We identified important disparities, as well as partial agreements, between five public zebrafish-to-human homology resources. There is still a need for standardized, comprehensive genomic mappings between zebrafish and humans. Without this, efforts to use zebrafish as a powerful translational research tool will be stalled.